Smaller visual arrays are harder to integrate in schizophrenia: Evidence for impaired lateral connections in early vision. (December 2019) - Keane, Brian P.; Paterno, Danielle; Crespo, Laura P.; Kastner, Sabine; Silverstein, Steven M.
Abstract: Long-range horizontal connections in early vision undergird a well-studied "collinear facilitation" effect, wherein a central low-contrast target becomes more detectable when flanked by collinear elements. Collinear facilitation is weaker in schizophrenia. Might lateral connections be responsible? To consider the possibility, we had 38 schizophrenia patients and 49 well-matched healthy controls judge the presence of a central low-contrast element flanked by collinear or orthogonal high-contrast elements. The display (target+flankers) was scaled in size to produce a lower and higher spatial frequency ("SF") condition (4 and 10 cycles/deg, respectively). Larger stimulus arrays bias processing towards feedback connections from higher-order visual areas; smaller arrays bias processing toward lateral connections. Patients had impaired facilitation relative to controls at higher but not lower SFs. Combining data from a past study on "contour integration" (in which subjects sought to detect chains of co-circular elements), we found correlated integration and facilitation performance at the higher SF and a similar effect of spatial scaling across SF, suggesting a common mechanism. In an exploratory analysis, worse contrast thresholds (without facilitation) correlated strongly with more premorbid dysfunction. In schizophrenia, inter-element filling-in worsens at smaller spatial scales potentially because of its increased reliance on impaired lateral connections in early vision.